Comparison of Geological Structures and Satellite-based Tectonic Lineaments in Gülağaç (Aksaray) and its Surroundings - Ramazan Demircioğlu (Hittite Journal of Science and Engineering)

(untitled)
The study area covers the Gülagaç district of Aksaray and its surroundings in the Central Anatolia region of Turkey. The basement of the study area consists of metamorphic rocks belonging to the Paleozoic–Mesozoic-aged Kaman Group. Mesozoic-aged ophiolites overlie these rocks, and both are cut by Late Cretaceous-aged igneous rocks. These units were then overlain by Palaeocene-Quaternary-aged volcanic and sedimentary units. The region has important geological structures that have undergone polyphase deformation, especially in the Eocene units. As a result of these deformations, faults, fractures, folds and linearities were formed. . These structures were compared with satellite-based tectonic lineaments, and it was observed that the general orientations of the lines determined in the field and the satellite-based lineaments were largely compatible. The results of this study can make an important contribution to the exploration of mineral and geothermal resources in the region.